PENGARUH PENGETAHUAN DEWAN TENTANG ANGGARAN, PARTISIPASI MASYARAKAT, TRANSPARANSI KEBIJAKAN PUBLIK DAN AKUNTABILTAS PUBLIK TERHADAP PENGAWASAN KEUANGAN DAERAH - Niza Bahruna; Naz’aina Naz’aina; Muhammad Haykal (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to empirically examine the effect of the council's knowledge of the budget, public participation, public policy transparency and public accountability on the regional financial control of Bireuen Regency. The data used are primary, secondary and interview data. Data obtained through the distribution of questionnaires to research respondents. The population in this study were all members of the Bireuen Regency DPRD for the 2019-2024 period, Budget Users (PA) and Financial Management Officers (PPK) in all Regional Government Organizations (OPD) and the community. The sample in this study used the census/saturated sample method for members of the DPRD of Bireuen Regency for the 2019-2024 period and all local government organizations (OPD). Meanwhile, the community sample used purposive sampling consisting of Non-Governmental Organizations (NGOs), community leaders, community organizations, academics, students and the mass media. The data analysis method uses multiple regression analysis method using SPSS 23 Software program. The partial test results show that there is a positive and significant relationship between the variables of the Council's Knowledge of Influential Budgets, public participation, transparency of public policies and public accountability for the Regional Financial Supervision of Bireuen Regency.